Թուրքիայի հարաբերությունները Մաղրիբի արաբական երկրների հետ տարածաշրջանային և գլոբալ զարգացումների համատեքստում 1989-1995թթ. - Արմեն Ժամհարյան (ՀՀ ԳԱԱ հրատ.)
During 1989-1995 in the relationship of Turkey-Maghreb Arabic countries a new field of correlation is seen, that is the trend of membership in territorial and international structures and the regulation and tightening of the relationships in the range of these structures.
Keywords: Modern History; International relations